Effect of Laser Energy on Anisotropic Material Properties of a Novel Austenitic Stainless Steel with a Fine-Grained Microstructure - Yurong Wang; Buwei Xiao; Xiaoyu Liang; Jun Zhou; Feng Lin (Journal of Manufacturing and Materials Processing)
Laser powder bed fusion (LPBF) provides a novel approach with high complexity and freedom for material processing and design, and its special thermal history endows the material with anisotropic properties. By adding micro-alloying elements Nb and Ti into conventional 316L, the anisotropy of the novel austenitic stainless steel fabricated by LPBF, which is related to the laser heat input, was investigated. The refined microstructure of this steel was further strengthened with in situ-generated Nb-, Cr-, and Ti-rich nanoprecipitates at a specific location. The heat input affects the material anisotropy, and a lower heat input leads to stronger anisotropy in this steel. The as-built parts at a low heat input in the horizontal and vertical planes exhibited finer microstructures compared to those fabricated at a high heat input. The epitaxial growth of the grains associated with the thermal gradient resulted in the vertical-section grain size being generally larger than that of the horizontal section. As a result, the low-heat-input parts with a finer grain are also stronger in the horizontal direction, with yield and tensile strengths approaching 0.9 and 1.2 GPa, respectively. Meanwhile, the microstructural changes due to the high heat input imparted a better ductility of parts in different sections (a 3.15% and 4.4% increase in the horizontal and vertical directions, respectively). Its mechanical properties depend mainly on the direction of stress coupled with intergranular friction during deformation in both coarse and fine grains.